Biological hydrogen gas production from gelatinaceous wastewater via stand-alone circular dark/photo baffled fermenter. (January 2019) - Meky, Naira; Fujii, Manabu; Ibrahim, Mona G.; Tawfik, Ahmed
Abstract: The novel lab-scale stand-alone circular dark/photo baffled reactor (SCBR) was developed for the treatment of synthetic gelatinaceous wastewater and the enhancement of biohydrogen production (H2 ) using mixed microbial culture. The pilot system was operated at a constant hydraulic retention time (HRT) of 48 h with an organic loading rate of 1.3 gCOD/L/day and pH value of 6.5 ± 0.2. The results showed that the SCBR which consists of four compartments (C1, C2, C3, and C4) was efficient for the removal of chemical oxygen demand (COD). The total COD removal efficiency was recorded to be 78 ± 13% and the production rate of H2 was enhanced. The total HPR of SCBR was 14 ± 0.7 L/day. The results revealed that the production rate of volatile fatty acids (VFAs) by dark fermentation was much higher than the consumption rate by photofermentation, and VFAs production did not inhibit the H2 production or the treatment performance of SCBR.